2011
DOI: 10.1038/gt.2011.20
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic gene therapy prolongs survival of corneal endothelial cells during storage

Abstract: Corneal transplantation is the most common form of grafting performed worldwide. Corneal endothelial cells (EC) form a monolayer in the posterior portion of the cornea and are essential for corneal transparency. EC loss during storage prior to transplantation is a principal reason for rendering donor tissue unsuitable for transplantation, and apoptosis has been shown to be the major contributor to EC loss during storage and after transplantation. Therefore, the potential use of anti-apoptotic gene therapy to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 33 publications
(41 reference statements)
0
39
0
5
Order By: Relevance
“…Previous studies demonstrated that Bcl-xl was down-regulated in ECs apoptosis induced by Ang II (11), endostatin (35), hypoxia (36) and hypoxia/reoxygenation (25) . To the contrary, over-expression of Bcl-xl was able to protect ECs from apoptosis mediated by DNA damaging agent and pro-inflammatory cytokines (37). Identifying the factors that regulate Bcl-xl levels is of paramount importance for better maintaining ECs viability and developing more effective therapies for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that Bcl-xl was down-regulated in ECs apoptosis induced by Ang II (11), endostatin (35), hypoxia (36) and hypoxia/reoxygenation (25) . To the contrary, over-expression of Bcl-xl was able to protect ECs from apoptosis mediated by DNA damaging agent and pro-inflammatory cytokines (37). Identifying the factors that regulate Bcl-xl levels is of paramount importance for better maintaining ECs viability and developing more effective therapies for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data, for example, suggest that the endothelium of human corneas treated with the anti-apoptotic gene p35 survives longer than untreated cells. 29 Clinical advances in gene therapy have shown that viral vectors can deliver genes safely to several tissues and the promising initial results from a number of clinical trials suggest that certain diseases may potentially be treatable. Successful delivery of therapeutic meganucleases to human corneas ex vivo was achieved here for the first time, highlighting the possibility of delivering genetic material or therapeutic molecules to the corneal endothelium using non-integrating rAAV2/1.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, the most recent gene therapy applications to prevent immune-mediated corneal allograft rejection will be briefly summarised (table 1). Genetic modification of corneal tissues with the view of improving endothelial viability during storage has been published recently [7,8]. However, gene therapy for endothelial protection or for treatment of corneal diseases has been reviewed recently and will not be discussed in this review [9,10].…”
Section: Genetic Modification Of Corneal Allografts Prior To Transplamentioning
confidence: 99%